Depressive symptoms among final year student: a study of gender differences - Lim, Chin Fen; Norsimah Dasan (Unit Penyelidikan Psikologi dan Kesihatan Sosial UMS, 2020)
The prevalence of depression among university students, especially final year students, is increasing. However, different gender shows a different degree of depressive symptoms. Hence, the researcher studied the significant differences in depressive symptoms among different gender of final year students in University Malaysia Sabah (UMS), Kota Kinabalu. Final year students from Faculty of Medicine & Health Sciences (FMHS), Faculty of Food Science & Nutrition (FFSN), Faculty of Business, Economics & Accountancy (FBEA), and Faculty of Social Sciences & Humanities (FSSH) completed the survey measuring depressive symptoms (Center or Epidemiologic Studies Depression Scale (CES-D)) through online. This study using cluster random sampling, and 150 students who had participated (53.3% female and 46.7% male). The mean age of the participants was 23.15 years. The descriptive result showed final year students have a high level of depressive symptoms, which a mean is 36.97 (SD = 12.41). The independent-samples t-test result showed a significant difference between males and females in depressive symptoms (p < .05). These findings are supported by several previous studies and discuss important aspects related to gender roles, especially among university students. The potential explanations for this finding include the physiological factor, personality, and environment factor. The implication of the research’s findings has contributed knowledge to the field of depressive symptoms. Also, the Ministry of Education may give more attention to and help vulnerable students, especially female students. For future research, university students from other states or areas should be included to generalize the result. In conclusion, females are vulnerable to the social setting. Therefore, to decrease the incidence of depressive symptoms in females, the entire society, but not only the people around them, have the responsibility to help females to deal with distress mood.